2014
DOI: 10.3109/0167482x.2014.992410
|View full text |Cite|
|
Sign up to set email alerts
|

Testing direct and moderating effects of coping styles on the relationship between perceived stress and antenatal anxiety symptoms

Abstract: The findings of this study highlight the direct and moderating effects of coping styles. This knowledge is important to healthcare professionals in planning health service provision. Health services should dedicate resources to teaching pregnant women how to enhance PC styles, alter NC styles and cultivate optimistic thinking to alleviate anxiety symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Yan et al [ 13 ] investigated the effect of coping style on the relationship between perceived stress and psychological distress and found that positive coping style alleviated individuals’ emotional distress, while negative coping did the opposite. The results was consistent with most related-topic researches, with positive or adaptive coping being associated with lower levels of anxiety and depression, and negative or maladaptive coping exacerbating psychological distress of people [ 14 16 ]. Additionally, a review of stress-related mood disorders suggested that differences in coping styles directly leaded to differences in individual physiological responses to stressors, which in turn affected individual susceptibility to illness [ 17 ].…”
Section: Introductionsupporting
confidence: 89%
“…Yan et al [ 13 ] investigated the effect of coping style on the relationship between perceived stress and psychological distress and found that positive coping style alleviated individuals’ emotional distress, while negative coping did the opposite. The results was consistent with most related-topic researches, with positive or adaptive coping being associated with lower levels of anxiety and depression, and negative or maladaptive coping exacerbating psychological distress of people [ 14 16 ]. Additionally, a review of stress-related mood disorders suggested that differences in coping styles directly leaded to differences in individual physiological responses to stressors, which in turn affected individual susceptibility to illness [ 17 ].…”
Section: Introductionsupporting
confidence: 89%
“…By contrast, the results regarding the effect of problem-focused and emotion-focused copings are mixed. Usually, these strategies can be associated with better maternal adjustment and child outcomes [ 1 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In such times, social support is a buffer against negative effects. Studies show that pregnant women who have social support, despite the stress level, experience less pregnancy complications [7,9,10,15,16]. Sygulla et al (2009), based on research conducted among pregnant women attending childbirth classes, found that future mothers showed a very high need for social support and obtained it in 87.5% from the partner, in 62.5% from the parents, 62.5% from the doctor, and 53.1% from a friends [17].…”
Section: Discussionmentioning
confidence: 99%